On the Origin of European Imbalances in the Context of European Integration - Carrasco, Carlos A.; Peinado, Patricia (Panoeconomicus, 2015)
We study the origin of European imbalances in the context of European integration. As a whole, the European Union and Eurozone have had nearly balanced external accounts. However, member countries have presented divergent positions. We analyse the short-term and medium-term factors underlying the presence of European external imbalances. Our results reveal the existence of divergent trends in key macroeconomic variables within the Eurozone. Moreover, the current account (CA) responds in the short-term to real unit labour cost (ULC) and discretionary fiscal policy. However, we point out the possible existence of a structural component of the CA. When assessing the medium-term determinants of the CA imbalances, catching-up, old-age dependency ratio and country-level specialisation (non-price competitiveness) are relevant variables explaining those imbalances. Key words: Current account, European imbalances, European integration, Competitiveness, Catching-up. JEL: E61, E62, E65, H62, H63.